The genomic regulatory elements for estrogen receptor alpha transactivation‐function‐1 regulated genes. Issue 12 (16th October 2020) - Arao, Yukitomo; Hamilton, Katherine J.; Grimm, Sara A.; Korach, Kenneth S.
Abstract: Estrogen receptor alpha (ERα) is a ligand‐dependent transcription regulator, containing two transactivation functional domains, AF‐1 and AF‐2. The selective estrogen receptor modulators (SERMs), including 4‐hydroxytamoxifen (4OHT), activate AF‐1 preferentially rather than AF‐2. However, it is unclear whether this specific function is related to the tissue‐selective functionality of SERMs. Moreover, there is no information determining AF‐1–dependent estrogenic‐genes existing in tissues. We sought to identify AF‐1–dependent estrogenic‐genes using the AF‐2 mutated knock‐in (KI) mouse model, AF2ERKI. AF2ER is an AF‐2 disrupted estradiol (E2)‐insensitive mutant ERα, but AF‐1–dependent transcription can be activated by the estrogen‐antagonists, fulvestrant (ICI) and 4OHT. Gene profiling and ChIP‐Seq analysis identified Klk1b21 as an ICI‐inducible gene in AF2ERKI uterus. The regulatory activity was analyzed further using a cell‐based reporter assay. The 5′‐flanking 0.4k bp region of Klk1b21 gene responded as an ERα AF‐1–dependent estrogen‐responsive promoter. The 150 bp minimum ERα binding element (EBE) consists of three direct repeats. These three half‐site sequences were essential for the ERα‐dependent transactivation and were differentially recognized by E2 and 4OHT for the gene activation. This response was impaired when the minimum EBE was fused with a thymidine‐kinase promoter but could be restored by fusion with the 100 bp minimum transcription initiation element (TIE) of Klk1b21, suggesting that the cooperative function of EBE and TIE is essential for mediating AF‐1–dependent transactivation. These findings provide the first in vivo evidence that endogenous ERα AF‐1 dominant estrogenic‐genes exist in estrogen‐responsive organs. Such findings will aid in understanding the mechanism of ERα‐dependent tissue‐selective activity of SERMs.